Work fatigue in people who worked at home during times of confinement by COVID-19 - Barreto-Osma, Doris Amparo; Rojas-Castro, Slendy Xiomara; Uribe-Barrera, Daniela Alejandra (Universidad y Salud, 2021)
Introduction: The social isolation triggered by the COVID-19 pandemic forced employees to work from home and experience diverse feelings, which together with labor factors as well as physical, emotional, and/or mental demands, led to work fatigue and in turn, to health consequences. Objective: This study was aimed at identifying symptoms related to labor fatigue in people working from home due to COVID-19. Materials and methods: A quantitative study with a descriptive-cross sectional approach. Data was collected from 511 participants who worked at home using a labor fatigue virtual scale and the informed consent. Results: 47.7% of participants experienced a medium fatigue level, in dimensions such as physical load, mental load, psycho-physiological effects, and perception of changes in job dynamics. Likewise, they reported negative experiences associated with job dissatisfaction and health issues. On the other hand, positive events were identified, such as sharing time with family, job autonomy, and learning experiences. Conclusions: Work related fatigue was evidenced in half of the participants, which was expressed through symptoms associated with different dimensions. They were perceived frequently and may affect the quality of life of participants if these symptoms are not treated properly.